Compressive behavior and damage evaluation of a PBX substitute material. Issue 9 (4th July 2017) - Chen, Lin; Han, Dong; Bai, Shu-Lin; Zhao, Feng; Chen, Jian-Kang
ABSTRACT: In this work, a polymer-bonded explosive (PBX) substitute material was made of sugar granules and polymer binder with a weight proportion of 90:10. The damage evolution and mechanisms under monotonic and repeated compression were studied in detail by adopting radiation x-ray computed tomography, scanning electronic microscopy, and a laser particle size analyzer. It is found that the initial pores and cracks from the granule breaking represent the main mechanisms of damage. The granule size and porosity decrease, while the damage parameter increases with the increasing applied strain. They are responsible for the damage evolution described by damage parameter D as a function of applied strain. The microscopic observation and macroscopic measurements are correlated quantitatively, which reveals the compressive behavior of the PBX substitute material.